YOUR LANGUAGE YOUR CHARACTER - Saleh, Mursid (Language Circle: Journal of Language and Literature, 2014)
The main function of any language is to express ideas, thoughts, and feelings. These being characteristic properties of human beings, the language a human being uses will ultimately reflect what is characteristic of him or her. Good language reflects good characteristics of the user, and vice-versa. Learning being another characteristic property of human beings, the language one learns shapes and is shaped by his or her personal characteristics. As character is the accumulation of oneâs personal characteristics, there are good reasons to suggest that while one is learning and using a language, he take good care so that good character is reflected. In that way communication will be properly conducted and interpersonal relationships properly established.